Perbandingan Pidana Mati dalam Perspektif Hukum Islam dan Hukum Pidana Indonesia - Saharuddin, Saharuddin; Rasyid, Muh. Fadli Faisal (Amsir Law Journal, 2022)
We are all aware that death awaits us, the problem here is when and how we are picked up by death itself. For most humans, death is a very scary event, but there are also those who are picked up by death in a state of calm and peace. What about those whose deaths are decided by fellow human beings, this has always been a difference between society in general and scholars in particular. From year to year and even now, discussions about the pros and cons of imposing the death penalty continue to be an endless discussion. On the one hand, the death penalty is considered to be effective in deterring perpetrators, but on the other hand, the implementation of the death penalty is like usurping the author's authority. Indeed there is no statistical evidence that crime will decrease if the death penalty is applied in a country. On the other hand, if it is not applied, it has not been proven that in a country crime is increasing.